Optimalisasi Pit Limit Penambangan Mineral Nikel Laterit PT ANTAM Tbk. Unit Bisnis Penambangan Nikel Di Site Pomalaa Sulawesi Tenggara Di Front X - Fitratul Rahmi; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Take into account mining optimization by taking into account the NPV value as the main reference factor of the Ultimate Pit Limite (UPL) that is used based on the division of levels obtained by comparing the sale value or the Net Present Value (NPV) of the Laterite Nickel Laterit. Inverse Distance Weighting (IDW) Method. This method is an interpretation method with a simple block model approach by considering the surrounding points. The mining method that will be planned on Front X is an open pit method with a multi-tiered system. At PT ANTAM Tbk. UBPN Sultra makes block model based on division of levels which differentiates each zone. At Ni level <1.3 the layer is classified as waste or called top soil, Ni level <1.5 layer is still called waste or limonite while for the value of Ni level> 1.5 is called ore or saprolite The calculation of the Lerchs Grossmann dimension algorithm is basically the sum of costs and cumulative income in the pit limit. The modeling and calculation of the Grossmann Learch Method can be planned for a more optimal pit shape and in accordance with a more economical mining price. This method is far more complicated and the risk of human error is high to determine which pit is effective. This method considers all aspects.Keyword: Pit, Ultimate Pit Limit, Net Present Value (NPV), Nikel Laterit, Blok Model